Pengaruh Good Corporate Governance dan Konservatisme Akuntansi terhadap Kualitas Laba pada Perusahaan Indeks Value 30 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Lubis, Intan Nuraini; Siregar, Retnawari; Lores, Linda (Jurnal Akuntansi Nommensen, 2023)
The purpose of this study was to determine the effect of financial technology on the financial performance of banking companies listed on the Indonesia Stock Exchange in 2015-2022. This type of research is associative research, the population in this study are 44 all banking companies listed on the Indonesia Stock Exchange in 2015-2022. The sample in this study used a purposive sampling technique so that the sample size and population are the same, namely 40 financial reports for banking companies listed on the Indonesia Stock Exchange in 2015-2022. The type of data used in this study is quantitative data with secondary data sources, namely from the website of each company. The data collected was tested with descriptive statistical tests, classical assumption tests, simple linear regression, and hypothesis testing using SPSS. The results of this study indicate that financial technology has a positive and significant effect on the financial performance of banking companies listed on the Indonesia Stock Exchange in 2015-2022. The coefficient of determination is 28.70% so that it has an effect of 28.70% on banking financial performance. So that if the value of financial technology increases, it will improve the financial performance of banking companies listed on the Indonesia Stock Exchange in 2015-2022. Vice versa.